Heart failure and renal outcomes according to baseline and achieved blood pressure in patients with type 2 diabetes: results from EMPA-REG OUTCOME - Böhm, Michael; Fitchett, David H.; Ofstad, Anne Pernille; Brückmann, Martina; Kaspers, Stefan; George, Jyothis T.; Zwiener, Isabella; Zinman, Bernard; Wanner, Christoph; Marx, Nikolaus; Mancia, Giuseppe; Anker, Stefan; et al. (Journal of hypertension, 2020)
Background:  - The sodium-glucose co-transporter 2 (SGLT2) inhibitor empagliflozin reduced cardiovascular death or heart failure hospitalizations in type 2 diabetes (T2D) in addition to a reduction of SBP. As heart failure patients often present with low SBP, which can challenge treatment initiation, we explored if empagliflozin's effect on SBP was independent of baseline SBP and heart failure status, and if the effect on cardiovascular and heart failure outcomes was influenced by updated mean SBP or by an early change in SBP after drug initiation. - Methods and results:  - A total of 7020 patients were treated with empagliflozin 10 mg, 25 mg or placebo and followed for a median of 3.1 years. All of them had BP measurement at baseline. We evaluated changes in SBP in the context of heart failure status at baseline and according to baseline SBP categories (<120, 120--<130, 130--<140, 140--<160, ≥160 mmHg). The updated mean SBP during the trial was calculated as a time-dependent variable. We then assessed the association of baseline and updated mean SBP with three-point major adverse cardiovascular events (3P-MACE), hospitalization for heart failure, cardiovascular death, hospitalization for heart failure or cardiovascular death, all-cause death, and incident/worsening nephropathy, and whether treatment effect of empagliflozin vs. placebo on these outcomes differed if adjusted for updated mean SBP. Finally, we evaluated the impact of early decline in SBP (≥5 mmHg at week 4) on the treatment effect of empagliflozin vs. placebo on these outcomes. Analyses were performed via Cox regression adjusting for baseline risk factors including a term for treatment subgroup interaction, and by landmark analyses starting at week 4. The difference in SBP reduction at week 12 between empagliflozin and placebo was 3--5 mmHg and similar regardless of baseline SBP category or HF status at baseline. Baseline SBP and updated mean SBP categories showed no association with cardiovascular outcomes, but was associated with new/worsening nephropathy. The treatment effects of empagliflozin on all explored outcomes were independent of updated mean SBP as well of the early drop in SBP on treatment. - Conclusion:  - In addition to decreasing SBP, empagliflozin reduced cardiovascular, heart failure and renal outcomes independently of updated mean SBP during the trial, and of the early SBP drop. These results suggest a BP-independent effect of empagliflozin on cardiovascular and heart failure outcomes. - ClinicalTrials.gov identifier:  - NCT01131676.